Des Kaisers Piraten in der Südsee und im Südatlantik : Der Einsatz deutscher Hilfskreuzer in der ersten Phase des Ersten Weltkrieges. - Leipold, Andreas (Quellen und Forschungen zur Südsee. Forschungen., 2018)
The fighting in the Pacific during the First World War has long been neglected in research. The pirate journeys of the German auxiliary cruisers in the Pacific are negated to this day or covered by the idealized portrayal of Count Luckner and his auxiliary cruiser "Seeadler". This publication therefore deliberately sets itself apart from this type of historiography and also sees less successful German auxiliary cruisers in the years 1914 to 1915. In 1914, in addition to the German East Asia Squadron, auxiliary cruisers and auxiliary ships of the Reichsmarine were used in the Pacific: the auxiliary cruisers "Cormoran" and "Prinz Eitel Friedrich", the gunboat "Geier" and the survey ship "Planet" are the focus here of interest, from the war journeys over the internment period to the captivity of the crews in the United States of America. Aspects that have not been considered in the literature, such as the captivity of the crews, are described in detail. Without heroizing the author draws a realistic one s picture of the battlefields in the Pacific.